2013
DOI: 10.2147/ndt.s41596
|View full text |Cite
|
Sign up to set email alerts
|

Dalfampridine extended release tablets: 1 year of postmarketing safety experience in the US

Abstract: Background:Dalfampridine extended release tablets (dalfampridine-ER; prolonged-, modified, or sustained-release fampridine in some countries) were approved in the US to improve walking in patients with multiple sclerosis, as demonstrated by improvement in walking speed. Postmarketing safety experience is available from exposure of approximately 46,000 patients in the US from product approval through March 2011.Objective:To provide a descriptive analysis of all spontaneously reported postmarketing adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
6
10
0
Order By: Relevance
“…Fampridine-induced changes in clinical walking tests were not correlated with the self-assessed change in ambulatory performance in the double-blind core study (figure e-1 of long-term PR fampridine treatment. [15][16][17] The proportion of patients experiencing AEs and SAEs was in line with previous reports. 15,16 The frequency of AEs was not different between double-blind treatment with PR fampridine and placebo, indicating that PR fampridine was likely not responsible for the AEs in PwMS treated with the drug.…”
Section: Statistical Analysis Statistical Analysis Was Performed Witsupporting
confidence: 90%
“…Fampridine-induced changes in clinical walking tests were not correlated with the self-assessed change in ambulatory performance in the double-blind core study (figure e-1 of long-term PR fampridine treatment. [15][16][17] The proportion of patients experiencing AEs and SAEs was in line with previous reports. 15,16 The frequency of AEs was not different between double-blind treatment with PR fampridine and placebo, indicating that PR fampridine was likely not responsible for the AEs in PwMS treated with the drug.…”
Section: Statistical Analysis Statistical Analysis Was Performed Witsupporting
confidence: 90%
“…11 No new safety signals were observed, and, overall, TEAEs were consistent with what has been observed in previous controlled trials and in postmarketing surveillance. 1,2,4,5 In conclusion, this study provides evidence that dalfampridine-ER tablets, 5 mg twice daily, are not effective for improving walking in patients with MS. Although the primary endpoint of this study was not achieved, additional analyses with similarities to those used in previous trials showed that dalfampridine-ER 10 mg twice daily seems to be the minimally effective dose for improvement of walking.…”
Section: Practicepointsmentioning
confidence: 74%
“…3 Postmarketing safety data for 1 and 2 years suggested a safety profile in clinical practice similar to that observed in the clinical trials. 4,5 As part of the postmarketing commitment, evaluation of the efficacy and safety of a lower 5-mg dose of dalfampridine-ER tablets was required. The purpose of the present study was to evaluate the efficacy and tolerability of dalfampridine-ER 5 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…68 A total of four seizure-related adverse events were reported during the extension studies among the patients who were treated with dalfampridine-ER in the parent trial (1.5%); Descriptive analysis was performed to provide information on all postmarketing AEs that were spontaneously reported. 73 The most frequently reported AEs, with a prevalence of $2% of all reported cases and reported as the percent of total AEs, included dizziness (5.7%), insomnia (4.5%), balance disorder (3.9%), headache (3.2%), nausea (2.8%), urinary tract infection (2.4%), asthenia (2.0%), and back pain (2.0%). These were also the most common AEs reported during clinical development, and all are included in the current US product label.…”
Section: Tolerability Profilementioning
confidence: 99%